2020
DOI: 10.3390/e22080838
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Bitcoin Trends Using Algorithmic Learning Systems

Abstract: This research has examined the ability of two forecasting methods to forecast Bitcoin’s price trends. The research is based on Bitcoin—USA dollar prices from the beginning of 2012 until the end of March 2020. Such a long period of time that includes volatile periods with strong up and downtrends introduces challenges to any forecasting system. We use particle swarm optimization to find the best forecasting combinations of setups. Results show that Bitcoin’s price changes do not follow the “Random Walk” efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The rise in the value of cryptocurrencies in the digital asset market has promoted a number of studies aimed at investigating the dynamics of that market along with listing the major influence of channels. Research interests in cryptocurrency markets concentrate on the following issues: (1) accounting and value formation (Bouoiyour et al 2016 ; Blau 2017 ; Hayes 2017 ; Urquhart 2017 ; Zhu et al 2017 ; Sovbetov 2018 ; Bolt and Van Oordt 2019 ; Zimmerman 2020 ), (2) speculative bubbles, herding behavior, and lottery-like demand (Godsiff 2015 ; Poyser 2018 ; Grobys and Junttila 2021 ); and (3) forecasting cryptocurrency returns, volume, and price (Azari 2019 ; Bohte and Rossini 2019 ; Derbentsev et al 2019 ; Nasir et al 2019 ; Cohen 2020 ; Mudassir et al 2020 ). In addition, other studies focus on the volatility issue in the case of the relationship between the cryptocurrency market and gold and energy instruments (Huynh et al 2020a , b ; Huynh et al 2020a , b ; Thampanya et al 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rise in the value of cryptocurrencies in the digital asset market has promoted a number of studies aimed at investigating the dynamics of that market along with listing the major influence of channels. Research interests in cryptocurrency markets concentrate on the following issues: (1) accounting and value formation (Bouoiyour et al 2016 ; Blau 2017 ; Hayes 2017 ; Urquhart 2017 ; Zhu et al 2017 ; Sovbetov 2018 ; Bolt and Van Oordt 2019 ; Zimmerman 2020 ), (2) speculative bubbles, herding behavior, and lottery-like demand (Godsiff 2015 ; Poyser 2018 ; Grobys and Junttila 2021 ); and (3) forecasting cryptocurrency returns, volume, and price (Azari 2019 ; Bohte and Rossini 2019 ; Derbentsev et al 2019 ; Nasir et al 2019 ; Cohen 2020 ; Mudassir et al 2020 ). In addition, other studies focus on the volatility issue in the case of the relationship between the cryptocurrency market and gold and energy instruments (Huynh et al 2020a , b ; Huynh et al 2020a , b ; Thampanya et al 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They investigate a large set of covariates that cover nearly all important classes of financial assets, except bonds. They conclude that the intra-day distribution of daily returns follows a nonlinear memory process better captured by machine learning methods than conventional econometric models, which is further supported by a large body of literature that has documented related modeling exorcises [ 77 , 78 , 79 , 80 , 81 , 82 , 83 ].…”
Section: Applicationmentioning
confidence: 83%
“…In contrast to stock markets, cryptocurrencies are less regulated and therefore carry extra risks (Baek and Elbeck [9]). In such a dynamic trading environment, algorithmic trading systems can provide fast and useful information (Chow et al [10]; Liu et al [11]; Cohen [12]; Cohen [13]). Balcilar et al [14] found that when extreme events are excluded, volume is an important predictor of Bitcoin's price.…”
Section: Literature Reviewmentioning
confidence: 99%